Characterization of banana peels waste adsorbent for preliminary study of methylene blue removal from aqueous solution - M. Z. A., Zamri; Noor Yahida, Yahya; Raihan Syahirah, Ramli; Norzita, Ngadi; Widia, Mirta (IOP Publishing Ltd, 2019)
This paper presents the removal of methylene blue (MB) from aqueous solution using adsorbent produced from Banana peels waste (BPW). Banana peels waste adsorbent (BPWA) was prepared via carbonization in laboratory muffle furnace for 1 h. A preliminary study was performed on the adsorption reaction by varying the initial concentration of MB, adsorbent dosage, contact time, pH and temperature of the aqueous solution. Under the best conditions obtained, the maximum percentage removal of MB is approximately 99 %. The potential of BPWA as dyeing wastewater adsorbent was proven by Scanning Electron Microscopy (SEM) analysis, N2 adsorption-desorption analysis and Fourier Transform Infrared Spectroscopy (FTIR). From the results, the synthesized adsorbent shown a good percentage removal of MB. In addition, the optimum conditions for the adsorption study are 1 g of adsorbent in the 1 g L-1 of MB initial concentration, for 1 h at pH 8 in 65 ?C. This study reveals potential of BPW in removal of MB dyes from aqueous solution however, further studies are required to establish the applicability of the synthesized adsorbent for the treatment of wastewater from textile industry.